Formulasi Aspergillus sp. Sebagai Agen Pengendali Hayati Terhadap Phytopthora palmivora Butler. Penyebab Busuk Buah Pada Kakao (Theobroma cacao L.) Dalam Bentuk Sediaan Tablet - Mardiana Upara; Umrah Umrah; Alwi Alwi (Biology Department, Mathematics and natural science, Tadulako University, 2012)
The study about “Formulation on tablet of Aspergillus sp. bioantagonistic agent to Phytophthora palmivora Butler causing black pod disease of cocoa”, was done in the purpose or determining the best formula in Aspergillus sp. teblet formulation, and to determine it viability during 30 days of stronge. This experiment was conducted based on the Completely Randomized Design (CRD), with 8 tretmens and 3 replication. The treatments tested were P0 (100% of chaff), P1 (95 gr chaff + 5% bond supplement), P2 (90 gr chaff + 10% bond supplement), P3 (85 gr chaff + 15% bond supplement), P4 (80 gr chaff + 20% bond supplement), P5 (75 gr chaff + 25% bond supplement), P6 (70 gr chaff + 30% bond supplement), and P7(65 gr chaff + 35% bond supplement). The result showed that the viability of fungi, after 30 days stronge were 100%. The best formulation was P4 as determined based on brittleness test with score 6,73%, its higher than its other formula. Key words: Formulation, biological control agent, Aspergillus sp., and tablet.